Preventing Dementia Using Saffron, The Kampo Medicine, Kamiuntanto, and Their Combination, Kamiuntantokabankoka - Kuchta, Kenny; Aritake, Kosuke; Urade, Yoshihiro; Tung, Nguyen Huu; Yuan, Chun-Su; Sasaki, Yui; Shimizu, Koichi; Shoyama, Yukihiro (Frontiers in Pharmacology, 2022)
The Kampo formula Kamiuntanto (加味温胆湯), which is composed of 13 crude drugs, is well known for its anti-dementia activity. A significant increase of the choline acetyltransferase activity and mRNA level were observed in an in vitro test system. Kamiuntanto further ameliorates cholinergic shortage in the old rats. By testing variations of Kamiuntanto with one of its component drugs missing in each, Polygala radix was identified as the most essential component drug, most probably due to its saponins such as tenuifolin and sinapinic acid. Ginseng is also discussed as an essential component of Kamiuntanto in synergic function with Polygala radix. Saffron, which was already recommended in the Bencao Gangmu for spiritual functions such as memory and dementia, and is today used as an anti-spasmodic, anti-catarrhal, and nerve sedative herbal drug, is regarded as a further vital contributor to the pharmacological effect of Kamiuntanto. Saffron and its major constituent crocin enhance learning-memory, non-rem sleep and inhibit depression and neuronal cell death due to strong anti-inflammation activities. Based on the above literature data and an epidemiological survey for the treatment of sleeping disorder, depression, and dementia, we were able to demonstrate the indirect anti-dementia activity of crocin and saffron as well as Kamiuntantokabankoka (加味温胆湯加番紅花), its combination with the classical Kamiuntanto prescription.